Jarai clauses and noun phrases : syntactic structures in an Austronesian language - Jensen, Joshua (Pacific linguistics, 2014)
The first published treatment of the syntax of Jarai, an Austronesian language of Southeast Asia, this volume focuses on the noun phrase and three regions of the clause: the left periphery, inflectional elements, and the verbal domain. Close attention is given to pseudo-cleft questions and serial verb constructions. Phenomena are carefully described, then analyzed within the Minimalist framework.